2014
DOI: 10.9767/bcrec.9.2.5998.100-110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CaOZnO Nanoparticles Catalyst and Its Application in Transesterification of Refined Palm Oil

Abstract: The CaOZnO nanoparticle catalysts with Ca to Zn atomic ratios of 0.08 and 0.25 have been successfully synthesized by co-precipitation method. The catalyst was characterized by X-ray Diffraction (XRD) analysis provided with Rietica and Maud software, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FT-IR), and its properties was compared with bare CaO and ZnO catalysts. The phase composition estimated by Rietica software revealed that the CaO catalyst consists of CaO and CaCO3 pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…It indicated that ZnO active metal has been effectively impregnated in the CaO catalyst, it therefore affected the structure and characteristic of the catalyst. FTIR analysis on ZnO/CaO 6% was in accordance with the result of the work performed by Yulianti et al (2014), uttering that there are several functional groups found in the ZnO /CaO catalysts such as hydroxyl, carbonyl and ZnO groups. The summary of the FTIR interpretation was shown in Table 6.…”
Section: Ftir Analysis Of Zno/cao 6% Catalystsupporting
confidence: 83%
See 1 more Smart Citation
“…It indicated that ZnO active metal has been effectively impregnated in the CaO catalyst, it therefore affected the structure and characteristic of the catalyst. FTIR analysis on ZnO/CaO 6% was in accordance with the result of the work performed by Yulianti et al (2014), uttering that there are several functional groups found in the ZnO /CaO catalysts such as hydroxyl, carbonyl and ZnO groups. The summary of the FTIR interpretation was shown in Table 6.…”
Section: Ftir Analysis Of Zno/cao 6% Catalystsupporting
confidence: 83%
“…Figure 4 shown that ZnO/CaO 6% catalyst had a smaller structure compared to the CaO catalyst from eggshell which is presented in Figure 2. Moreover, ZnO/CaO 6% also demonstrated a denser and more solid structure Yulianti et al (2014), which found that the combination of ZnO and CaO exhibited uneven structure, and the catalyst shown solid form with different size.…”
Section: Sem-edx Analysis Of Zno/cao 6% Catalystmentioning
confidence: 97%
“…Pembuatan biodiesel dengan katalis homogen baik basa maupun asam memiliki beberapa kelemahan, antara lain pemisahan produk samping dengan katalis sulit dilakukan, terbentuknya produk samping berupa sabun dan limbah alkali memerlukan perlakuan lebih lanjut [10]. Katalis Heterogen mudah dipisahkan dari campuran laurtan, dapat digunakan kembali dan tidak bersifat korosif [11]. Dengan meninjau kekurangan tersebut maka dipilihlah katalis heterogen untuk proses pembuatan biodiesel.…”
Section: Hasil Dan Pembahasanunclassified
“…From the information of these spectrums, some bands in the ZnO/CaO spectrum were identified: stretching of O-H group in zinc hydroxide (3727 cm −1 ) and calcium hydroxide (3643 cm −1 ) formed by reaction with environmental water (Fujimori et al 2016), stretching of O-H (3424 cm −1 ) mainly by adsorbed water over a CaO surface (Yulianti et al 2014) and bands from 2800 to 2950 cm −1 which are associated with stretching of O-H in hydroxide structure with H-bonding (Fujimori et al 2016). Moreover, stretching of C=O in carbonates (1475 cm −1 ) formed by the reaction of the catalyst with carbon dioxide from environment as well as residual carbonates from co-precipitation, this process should be avoided because carbonates promote calcium leaching (Yulianti et al 2014). Finally, bending of Ca-O-H and Zn-O-H is observed from 870 to 850 cm −1 , but bands associated with stretching CaO and ZnO cannot be identified because they are overlapped.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
“…Within all the CaO-based catalysts, CaO and ZnO oxides show one of the best catalytic activities under moderate reaction conditions (Ngamcharussrivichai et al 2008;Kesic et al 2012;Klinklom et al 2013;Rubio-Caballero et al 2013;Istadi et al 2015;Chantara-arpornchai et al 2012;Lee et al 2014a, b;Yulianti et al 2014), where ZnO oxide may be useful to reduce the leaching process.…”
Section: Introductionmentioning
confidence: 99%